Curriculum leadership : strategies for development and implementation - Glatthorn, Allan A., 1924- 4 0 16; Boschee, Floyd.;Whitehead, Bruce M.; 5 (Los Angeles : Sage, 2009)
A comprehensive overview of curriculum development and implementation that discusses the nature and politics of curriculum, planning, improving the program of studies, the creation of new courses and units, evaluation, individualization, and other related topics.
Includes bibliographical references (p. 439-461) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Curriculum planning;Educational leadership;Educational leadership. -- United States.;United States; 20; 2